Patient Access to Care: In-Network and Out-of-Network Utilization of Services - Bethany G. Lanese; Nora Alrubaie (Ohio Journal of Public Health, 2022)
Background: Access to health care is impacted by several key factors such as urbanization, insurance coverage, availability of health care facilities, specialists, and equipment. For an in-depth understanding of Portage County area residents' health care utilization location choices, a study was conducted to identify the main factors and assess health care outmigration. Methods: A total of 125 292 patients were identified using 2019 administrative health data from University Hospitals Portage Medical Center in Portage County, Ohio. A descriptive analysis, t test, and chi-square tests were used to examine 3 primary outcomes: (1) patients’ demographics (age, gender, insurance, etc.), (2) time and distance patients are willing to travel for care, and (3) health services demand that is causing outmigration. Results: An analysis of 119 034 patients showed 66% of patients stayed in network and 34% went out of network. In-network participants had an average travel time of 30 minutes [95% CI, 29.5 to 29.8] and an average distance of 19.4 miles [95% CI, 15.9 to 16.1]. Conversely, out-of-network participants averaged 43 minutes [95% CI, 43.1 to 43.5] and 30.8 miles [95% CI, 30.4 to 30.8]. Outmigration was mainly influenced by the need for radiology services (66.3%), specifically mammograms (12.7%), computerized tomography (CT) (39.2%), and lab (18.2%). Conclusion: Outmigration can negatively impact a county's health care infrastructure and growth and contribute to a loss of revenue to the local hospitals. In this case, out-of-network services are more commonly used for radiology and lab work than for chronic conditions. It is recommended that both physicians and patients become knowledgeable about the impact of seeking out-of-network care
Keywords: Outmigration; Out-of-network; In-Network; Access to Care; Hospital service area